The Development of Organizations in a Laboratory - Guetzkow, Harold; Bowes, Anne E. (Management Science, 1957)
Does it seem feasible to attempt acceleration of the development of basic knowledge about organizations by utilizing the methodological advances which have occurred in the study of small groups? Specifically, how might the small group laboratory procedures of the social psychologist and sociologist be adapted to the study of organizations? Someday it may be possible to characterize social collectivities on a “meaningful set of orthogonal (independent) dimensions;” then “the definition of group and the discrimination of group from no-group [will] become arbitrary matters of convenience.” (1) In the meantime, it still seems fruitful to distinguish “small groups” from “organizations,” so that the extension of the methodologies from one area to the other is done with a modicum of circumspection. Groups are more or less stable configurations of persons in interaction. “Interaction” refers to the interlocking of the reactions of individuals to each other as stimulus objects.